Buying votes and international organizations - Axel Dreher; James Raymond Vreeland (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2011)
This study explores a basic idea in political economy: Trading money for political influence. Our focus is at the level of international institutions, where governments may exploit their influence in one organization to gain leverage over another. In particular, we consider the lending activities of the International Monetary Fund (IMF) and voting behavior at the United Nations Security Council (UNSC). Analyzing an original dataset on the successful and failed resolutions of the UNSC, we find evidence of vote-buying.
Keywords: O19; O11; F35; 330; IMF; UN Security Council; Voting; Aid; Internationale Organisation; Wahlverhalten; Public Choice; Internationaler Kredit; Welt